Comparison of Cochlear Implantation and Hearing Aid Use in Children with Severe-to-Profound Sensorineural Hearing Loss - Tanvi G., Wisp R., Sen D (Academic Journal of Clinicians, 2024)
Background Children with severe-to-profound sensorineural hearing loss face significant challenges in language development and communication. Cochlear implantation (CI) and hearing aids (HA) are two primary interventions, but their comparative effectiveness remains a topic of interest. Objective This study aims to compare the outcomes of cochlear implantation and hearing aid use in children with severe-to-profound sensorineural hearing loss. Methods A cohort of 80 children aged 2 to 10 years with severe-to-profound sensorineural hearing loss was recruited. The participants were divided into two groups: those using cochlear implants (n=40) and those using hearing aids (n=40). Outcomes were assessed through standardized language development assessments, audiometric evaluations, and quality of life questionnaires at baseline and 12 months post-intervention. Results Children with cochlear implants demonstrated significantly greater improvements in language development scores compared to those using hearing aids (p < 0.01). Additionally, the CI group reported higher levels of social engagement and improved quality of life metrics (p < 0.05). Audiometric evaluations revealed better sound discrimination abilities in the CI group. Conclusions Cochlear implantation offers superior outcomes in language development and quality of life for children with severe-to-profound sensorineural hearing loss compared to hearing aids. These findings support the consideration of cochlear implants as a primary intervention in this population.